El acto médico como ética de la relación (2009)
ABSTRACT: This documentary paper approaches the issue of the possible types of ethics that can be used in the medical practice, conceived as both therapeutic and ethical actions carried out by health professionals. It is concluded that medical action can be carried out as the expression of two main ethical approaches, namely: The instrumental ethics in which the discourse used by the professional during medical actions has an instrumental value. The second one is called intersubjective ethics, which considers that the aforementioned discourse has a special role, since it may restore the patient’s subjectivity and build a relational weave between the patient and the physician in which healing action can take place. It is concluded, in accordance with the second ethical approach, that medical vocation implies that physicians should develop a good, virtuous, and aesthetic life for themselves and for their patients.